Photosynthetic quotient relationship to inorganic nitrogen of rivers in Trengganu - Shamsuddin, Lokman (1983)
Photosynthetic quotient (P. Q) values with depth of rivers in Trengganu were found to be lowered by high levels of indigenous ammonium nitrogen, ranging from 1.2 -0.8, contrary to temperate conditions where high levels of nitrate increase the P. Q values from 1.5 to 2.0. This is attributed to the fact that nitrate, in lieu of ammonia, produces two extra molecules of oxygen per atom of nitrate nitrogen assimilated, culminating in higher P. Q values. Nevertheless, the present findings tally well with that of marine phytoplankton (ie. P.Q is 1.2) when ammonia is the prime source of nitrogen.